Online Shopping Experience and Its Impact on the Lifestyle Changes of Young Generations in Manado - Parengkuan, Chenry; Rantumbanua, Orentia; Rumondor, Nikita; Asaloei, Sandra Ingried (Asia Pacific Journal of Interdisciplinary Studies, 2025)
This research aims to explore the effects of lifestyle changes caused by the use of online shopping among adolescents and college students. A qualitative survey method was employed to collect data through in-depth interviews and analysis of participants' narrative experiences. The research findings indicate that online shopping has transformed the way adolescents and college students perceive the concept of shopping, enhancing convenience in their shopping experiences and influencing their purchasing decisions. Additionally, online shopping has also impacted social aspects, such as patterns of interaction with peers and the influence of fashion trends. The results of this study provide valuable insights into the lifestyle changes associated with the evolution of online shopping among adolescents and college students.